The global burden of women's cancers: a grand challenge in global health - Ginsburg, Ophira M; Bray, Freddie; Coleman, Michel P; Vanderpuye, Verna Dnk; Eniu, Alexandru; Kotha, S Rani; Sarker, Malabika; Huong, Tran Thanh; Allemani, Claudia; Dvaladze, Allison; Gralow, Julie; Yeates, Karen; et al. (© 2017 The Lancet, 2018)
This article was published in the Lancet [© 2016 Lancet ] and the definite version is available at : http://dx.doi.org/10.1016/S0140-6736(16)31392-7. The Journal's website is at: http://www.thelancet.com/journals/lancet/article/PIIS0140-6736(16)31392-7/abstract